The Influence of Audio-Visual Media on Students' Speaking Skills of the First Semester of PAI Program - Rizal, Syamsul (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This study explores the impact of audio-visual media on the speaking skills of the first semester students of PAI program, with a focus on fluency, pronunciation, and overall communication effectiveness. In recent years, the integration of multimedia tools, such as videos, films, and instructional content, has been recognized as a valuable resource in language learning. The research employs a mixed-methods design, combining quantitative assessments of fluency and pronunciation with qualitative interviews to capture students' perceptions. Over a six-week period, participants were exposed to a variety of audio-visual materials, and pre- and post-assessments were conducted to measure improvements in speaking performance. The results indicated a significant enhancement in students' fluency, pronunciation accuracy, and confidence in speaking. Furthermore, students reported increased comfort in engaging in conversations and public speaking after exposure to the media. These findings support the idea that audio-visual media provide authentic language models that help students internalize effective communication strategies. This study underscores the potential of audio-visual tools in fostering speaking skills and suggests that educators should incorporate these resources into language curricula to create a more dynamic and engaging learning environment.